2019
DOI: 10.2478/pjct-2019-0030
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic bioconversion of feather waste with keratinases of Bacillus cereus PCM 2849

Abstract: Enzymatic preparation from culture of keratinolytic Bacillus cereus PCM 2849 was applied for hydrolysis of whole chicken feathers, after sulphitolytic pretreatment. This process was optimized using a three-factor Box-Behnken design, where the effect of substrate concentration, sulphite concentration during pretreatment and reaction temperature was evaluated on the release of amino acids. Obtained results revealed the highest impact of reaction temperature, followed by substrate content and sulphite during pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…For instance, the biodegradation of chicken feather waste by B. aerius NSMk2 released 17 free AA, where eight were essential (Bhari et al, 2020). B. cereus PCM 2849 was able to release both essential and non-essential AA where the glutamic acid and proline were found at the highest concentrations (Ciurko et al, 2019). Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the biodegradation of chicken feather waste by B. aerius NSMk2 released 17 free AA, where eight were essential (Bhari et al, 2020). B. cereus PCM 2849 was able to release both essential and non-essential AA where the glutamic acid and proline were found at the highest concentrations (Ciurko et al, 2019). Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the different compositions of feathers and shafts. These amino acids are generally regarded as good nutritional feed additives . Especially, Thr is the second limiting amino acid in pig feed and the third limiting amino acid in poultry feed. , Supplementing the feed of juvenile piglets and poultry can promote livestock growth, improve meat quality, and reduce the cost of feed ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…Amino acid composition analysis of feather keratin hydrolysates revealed that glutamic acid and proline were the dominant products, as well as serine and glycine, and significant amounts of essential and branched-chain amino acids were also observed (Ciurko et al, 2019). Although porcine bristles demonstrate high mechanical strength, they were also hydrolyzed by keratinase from Amycolatopsis keratiniphila, with soluble proteins, small peptides, and free amino acids recovered (Falco et al, 2019).…”
Section: From Keratin Wastes To Valuable Productsmentioning
confidence: 99%